Development of Diorama Media in Science Subject for 5th Grade Elementary Student - Sulaiman; Faradita, Meirza Nanda; Naila, Ishmatun; Sadida, Qaulan (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Observations carried out by researchers in class V SDIT Ar Rayyan Surabaya found that the media used in the science and science subjects in class V SDIT Ar Rayyan did not use diorama media. This research aimed to determine the level of validity, effectiveness, and practicality of Terrarium Ecosystem Diorama media using the R&D method with the ADDIE model because the work stages are systematic, each phase is evaluated and revised, so the resulting product becomes a valid product. The data collection techniques used are validity, effectiveness, and practicality tests, use the following data collection techniques: Validation Sheet, Test Sheet, Student Response Sheet. Then the data analysis technique used is a descriptive analysis technique that calculates the percentage value of the results, the results is Terrarium Ecosystem Diorama Media gets a media validity value of 95.5% and a material validity value of 92.69%, which is the percentage included in the very valid category. Testing the effectiveness of this medium resulted in 85% of students achieving the KKTP score. This media practicality test received a percentage score of 84% and was included in the very practical criteria. Therefore, this Terrarium Ecosystem Diorama media can be stated as valid, effective, and practical.